The Structural Transformation of The Democratic Corporatist Model: The Case of Finland - Herkman, Juha (Javnost-The Public, 2009)
As in many other European countries, the Finnish political public sphere has been mediatised and commercialised over the last three decades at the same time that structural changes have taken place in the national media systems. By using Finland as an example, article considers the structural transformation of the “Democratic Corporatist Model” defi ned by Daniel C. Hallin and Paolo Mancini in their /Comparing Media Systems/ (2004). Article also examines what the Finnish case could bring to the discussions on the public sphere and its relation to empirical analysis in general.